Diagnostic Pitfall in [18F] FDG PET-CT: A Case Report on Transient Inflammatory Lung Uptake Mimicking Metastatic Rectal Cancer (Bangladesh Journal of Nuclear Medicine, 2026)
18F-FDG PET-CT is widely used in oncology for staging, treatment-response assessment and detection of recurrent or metastatic disease. However, its diagnostic specificity has limitations specially both infectious and inflammatory lesions may also demonstrate increased glucose uptake, thereby mimicking malignancy. We report a case of a 34-year-old man with rectal carcinoma who underwent 18F-FDG PET-CT after chemotherapy for response evaluation. The scan revealed a large glucose avid soft tissue density lesion in the right lung, raising strong suspicion for pulmonary metastasis or a second primary malignancy. Based solely on the image without the correlation of history, malignant aetiology was more likely. However, after clinical correlation further assessment suggested an infectious process. The patient was then treated with intravenous antibiotics and underwent follow up imaging. 18F-FDG PET-CT demonstrated complete resolution of the initial lesion confirming that the abnormality was actually infective consolidation rather a metastatic disease. This case highlights a significant challenge of interpretation of 18F-FDG PET-CT which is the distinction between malignant lesions and infectious or inflammatory processes. It shows the importance of careful clinical correlation, consideration of alternative aetiologies and follow-up imaging after a interval before confirming that diagnosis of metastasis. This approach is essential to avoid misdiagnosis, unnecessary invasive procedures, inappropriate treatment escalation, and incorrect staging of the cancer. The case also describes that 18F-FDG PET-CT is an essential tool not only for treatment monitoring but also for guiding clinical decision-making when interpreted along with full clinical correlation.Bangladesh J. Nuclear Med. 29(1): 111-115, 2026